Investigating Blockchain Technology’s Integration in Financial Services - Niu, Tianrun (Transactions on Computer Science and Intelligent Systems Research, 2024)
This paper introduces a comprehensive analytical framework designed to assess the efficacy of blockchain technology in financial accounting and its broader implications for the financial sector. The analysis explores how blockchain can revolutionize financial accounting by enhancing both efficiency and accuracy, facilitating real-time financial reporting, and expediting audit processes. It also examines blockchain’s current deployment across various financial domains, including insurance, banking, payment systems, asset trading, lending, and remittances, offering a detailed look at the technology’s penetration and impact. The study identifies significant hurdles, such as elevated transaction fees and prevailing technical constraints, which currently impede broader adoption. It also discusses potential regulatory challenges and the need for sector-wide collaboration to realize the full benefits of blockchain. The results of this study provide critical insights for both researchers and developers within the financial sector, highlighting the transformative potential of blockchain and proposing directions for future technological advancements and application areas. This examination not only underscores the immediate benefits and challenges but also sets the stage for subsequent innovation in integrating blockchain into established financial systems, potentially leading to more robust, transparent, and efficient financial services.